Execution of public spending and the human development index in districts of Huancavelica, 2019 - Yauri Condor, Mario Revelino (2022)
The objective of the research is to determine the relationship of the execution of public spending with the Human Development Index in the districts of the Huancavelica department, 2019, the hypothesis is whether there is a direct relationship between the execution of public spending with the Development Index Human in the districts of the Huancavelica department, 2019. The research methodology is of an applied type, explanatory level, descriptive, inductive, synthetic, analytical and dialectical method. The research design is non-experimental, cross-sectional, explanatory. The population is 100 districts of the department of Huancavelica. For statistical processing, information from the website of the United Nations Program and the National Center for Strategic Planning (Ceplan) was used. The main finding is that there is a weak positive relationship between the execution of public spending (earned per capita) and the Human Development Indices. Likewise, a worrying situation was found in the district of the province of Angaraes where there is a negative relationship between both variables, that is, in the districts with the highest execution of public spending (accrued per capita) there is also a lower Human Development Index.